1997
DOI: 10.1021/ja964210g
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ni(0)-COT Complexes, Displaying Semiaromatic Planar COT Ligands with Alternating C−C and CC Bonds

Abstract: Reaction of (R2PC2H4PR2)Ni(C2H4) with COT gives the mononuclear complexes (R2PC2H4PR2)Ni(η2-C8H8) (R = iPr 1a, tBu 1b). The COT ligand in 1a,b is planar with alternating C−C and CC bonds, corresponding to a formal semiaromatic [C8H8]- ligand. Reactions of 1a with (iPr2PC2H4PiPr2)Ni(η2,η2-C6H10) and of 1b with stoichiometric amounts of {(tBu2PC2H4PtBu2)Ni}2(μ-C6H6) or lithium afford the dinuclear complexes {(iPr2PC2H4PiPr2)Ni}2{μ-η4(1,2,5,6):η4(3,4,7,8)-C8H8} (2a) and {(tBu2PC2H4PtBu2)Ni}2(μ-η2:η2-C8H8) (2b; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 40 publications
1
60
0
Order By: Relevance
“…How ever, in more recent studies the structure of the transition states of the η 2 ,η 2 intra ring HRs in zero valent nickel complexes with arenes (see Scheme 1) were revised and the transition states were ascribed a η 4 hapticity 44 as for the transition state of the η 2 ,η 2 intra ring HRs in the struc turally similar η 2 complexes of COT. 14 According to our DFT calculations, the η 2 ,η 2 intra ring HRs in structures 1A and 1B result in the complexes 1C and 1D, respectively, which are slightly different in energy from each other and from the initial complexes 1A and 1B owing to different mutual arrangement of bulky isopropyl groups and different conformations of the metallacycle.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…How ever, in more recent studies the structure of the transition states of the η 2 ,η 2 intra ring HRs in zero valent nickel complexes with arenes (see Scheme 1) were revised and the transition states were ascribed a η 4 hapticity 44 as for the transition state of the η 2 ,η 2 intra ring HRs in the struc turally similar η 2 complexes of COT. 14 According to our DFT calculations, the η 2 ,η 2 intra ring HRs in structures 1A and 1B result in the complexes 1C and 1D, respectively, which are slightly different in energy from each other and from the initial complexes 1A and 1B owing to different mutual arrangement of bulky isopropyl groups and different conformations of the metallacycle.…”
Section: Methodsmentioning
confidence: 76%
“…The limiting spectrum is not observed even at 173 K. It follows that the activation barrier to η 2 ,η 2 intra ring HR is at most 5 kcal mol -1 . It was as sumed 14 that the rearrangement proceeds via a transition state with a higher hapticity compared to that of the initial complex (η 4 vs. η 2 , respectively). Intra ring HRs in com plexes with various cyclopolyolefins may proceed by the [1,2] or [1,3] metal shift mechanisms; 15 in addition, η 2 ,η 2 intra ring HRs may proceed as combinations of these two processes.…”
Section: Methodsmentioning
confidence: 99%
“…The low natural atomic charges of q ptC = -0.33 |e| and q Pd = +0.50 to +0.51 |e| suggest that the ptC-Pd interactions are mainly covalent in C s 2. (3) 2-dianion [14] at the same B3LYP level. The C-C bond-length alternation in [C n H n ]M 4 C[C nЈ H nЈ ] complexes studied in this work is related to the fact that each periphery transition metal atom in these M 4 C square sheets is coordinated in a η 2 mode to two C=C pπ-pπ bonds above and below it (see Figure 1) [8a,15] PtC serves as a σ-acceptor and a π-donor in planar tetra-and hypercoordinate carbon systems.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The natural consequence of this approach was the assumption according to which the free COT 22 ion is also aromatic. For instance, Bach et al 17 report that COT 22 exhibits a fully aromatic character, adopting a delocalized structure with bond length of 1.41 Å and the D 8h symmetry. In their article, Bach et al refer to an earlier work by Trindle et al 5 in which this fully aromatic D 8h structure was reported on the basis of theoretical calculations performed on the semiempirical level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is remarkable that planar COT rings can also be found in metal complexes. [11][12][13][14][15][16][17][18][19] This article has been dedicated to Prof. Tadeusz Marek Krygowski in recognition of his significant contribution to the field of computational organic chemistry.…”
Section: Introductionmentioning
confidence: 99%